Labour supply and firm size - Lin Shao; Faisal Sohail; Emircan Yurdagul (Bank of Canada, 2023)
Larger firms feature i) longer hours worked, ii) higher wages, and iii) smaller (larger) wage penalties for working long (short) hours. We reconcile these patterns in a general equilibrium model, which features the endogenous interaction of hours, wages, and firm size. In the model, workers willing to work longer hours sort into larger firms that offer a wage premium. Complementarities in hours worked generate wage penalties that increase with the distance from the average firm hours. We use the model to argue about the importance of the interaction between hours, wages, and firm size on inequality.
Keywords: E24; J2; J31; 330; Firm dynamics; Labour markets